Effect of constructive direction on precision of temporary bridges using 3D printers with SLA, DLP, LCD and 4k technology - Ibáñez, Claudio Arturo Antonio (2022)
Fil: Ibañez, Claudio Arturo Antonio. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Prostodoncia I A; Argentina.